Re-Imagining the African "Local Community" in Social Research: Lessons from Mbagen Development Association of Benue State - Terna, Vincent Tavershima; Afaha, Philip; Golwa, Joseph (Kashere Journal of Politics and International Relations, 2025)
In Africa, community development is viewed as a holistic approach encompassing various sectors such as agriculture, education, housing, health, and employment. While there is considerable evidence of global approaches to development, research documenting the efficacy and impact of local approaches remains scarce. This study explores the developmental initiatives undertaken by the Mbagen Development Association (MDA), a local community in Benue State, aimed at addressing the needs and aspirations of its populace – with a specific focus on health and education. This study employed qualitative research methods, including participant observation and in-depth interviews with key stakeholders within MDA. By engaging directly with members of the community and documenting their experiences, a comprehensive understanding of MDA's developmental activities in health and education was achieved. Furthermore, the study revealed the effective approaches to community development in Mbagen, Buruku local government area of Benue state, particularly in the critical areas of health and education and the impact of such developmental efforts were discussed. Potential challenges encountered by MDA in the cause of her developmental efforts were highlighted. One of the findings of this study among others was that there is a formidable community development association in Mbagen called Mbagen Development Association (MDA). The paper recommended among other recommendations that wealthy sons and daughters of Mbagen should continue to donate huge amount of money to the association so that more projects could be executed for benefit of Mbagen community.